Crystallization behavior of PEG/PLLA block copolymers: Effect of the different architectures and molecular weights. (7th April 2015) - Zhou, Dongdong; Shao, Jun; Li, Gao; Sun, Jingru; Bian, Xinchao; Chen, Xuesi
Abstract: PEG/PLLA block copolymers bearing various number of arms were synthesized. The molecular weights of PLLA in the block polymers were determined by 1 H NMR and GPC. For 1-arm, 2-arm, 4-arm PEG/PLLA block copolymers, DSC and WAXD results indicated that the different architectures and compositions of the block copolymers didn't alter the structures of PEG and PLLA crystallites, but markedly affected the crystallinities and melting temperatures of PEG and PLLA. The critical M n, PLLA of each arm decreased with the number of arms increasing ( M n, MPEG5-PLLA  >  M n, 2PEG10-PLLA  >  M n, 4PEG20-PLLA ), when the PEG crystallites were not detected. As M n, PLLA of each arm was similar in the copolymers, T m, PEG and X PEG decreased gradually with the number of arms increasing, and the similar regularities also displayed for PLLA. The crystallization behavior and the variation architectures of PEG/PLLA copolymers can provide primary data to the applications in the drug delivery and industry parts. Graphical abstract: Highlights: PEG/PLLA block copolymers with different architectures were synthesized. The different architectures did not alter the crystal structures of PEG and PLLA. The effect of architectures was markedly on the crystallization behavior of PEG and PLLA. A mode of the confined environment of PEG in the PEG/PLLA block copolymers with different architectures was suggested.